Descriptive epidemiology of the cholera outbreak in Zimbabwe 2018–2019: role of multi-sectorial approach in cholera epidemic control. Issue 1 (30th January 2023) - Mashe, Tapfumanei; Chaibva, Blessmore V; Nair, Parvati; Sani, Khalil A; Jallow, Musa; Tarupiwa, Andrew; Goredema, Alexander; Munyanyi, Manes; Chimusoro, Anderson; Mpala, Nkosilathi; Masunda, Kudzai P E; Duri, Clemence; et al.
Abstract : Objectives: This study was conducted to explore the epidemiology and microbiological pattern of the cholera outbreaks that occurred in Zimbabwe from 2018 to 2019. Study setting and design: This descriptive study used secondary data of 9971 out of 10 730 suspected cases from the Zimbabwean National Diseases Surveillance system and microbiology data of 241 out of 371 patients from the National Microbiology Reference Laboratory in Harare, for the period 5 September 2018 and 3 January 2019. Descriptive analysis was performed to describe the characteristics of the outbreak in terms of person, place and time. Results: A cumulative total of 10 730 suspected, 371 laboratory-confirmed cholera cases and 68 deaths were reported in Zimbabwe through the situation analysis report (sitrep). The attack rate during the outbreak was 174.6 per 100 000 with a case fatality rate of 0.63%. Most cases seen were among adults from Harare province. Antimicrobial sensitivity testing results showed that a multidrug resistant strain of Vibrio cholerae O1, Ogawa serotype was responsible for the outbreak. The treatment of cases was changed from the standard recommended medicine ciprofloxacin to azithromycin as confirmed by the antimicrobial sensitivity test results. Strategies employed to contain the outbreak included mass oral cholera vaccination in the hotspot areas of Harare, provision of improved and appropriate sanitation measures, provision of safe and adequate water, chlorination of water and improved waste management practice. Conclusions: The recurrence of a cholera outbreak is a global concern, especially with the emergence of multi-drug resistant strains of the causal organism. Improving water, sanitation, hygiene infrastructure, health system strengthening measures and inter-sectoral collaboration in responding to the cholera outbreak was key to controlling the outbreak.